Gender Mainstreaming dalam Kebijakan Pendidikan Islam Tahun 2010-2014 - Ainur Rofiah (Islamica: Jurnal Studi Keislaman, 2016)
This article examines the gender mainstreaming in Islamic education policy for 2010-2014 adopted by the Ministry of Religious Affairs of the Republic of Indonesia. Using a qualitative descriptive approach, this article explores the extent of the strategic plan of the Ministry of Religious Affairs in 2010-2014, especially policies that are gender neutral and gender responsive policies. The author under-lines that the government needs to undertake the planning policies or programs that are more responsive to gender. One of the strategies adopted to fulfill the practical and strategic needs in this context is through Gender Mainstreaming which is implemented in relevant and signifi-cant programs. The author also asserts that Gender Mainstreaming in Islamic education is very necessary. Norms that have been frequently used as a reference for the gender policy should be reconsidered. This is to ensure that policies are drawn right on target, though—all parties must realize that—the uniform policy cannot necessarily be applied because of gender roles, however, differ both between places, time and socio-economic class.